OVERWEIGHT, ABDOMINAL OBESITY AND THE EXCESSIVE FAT RELATING TO THE BODY MASS OF THE MEMBERS OF YMCA (Fiep Bulletin - online, 2013)
The aim was this studied examine the frequencies of overweight, abdominal obesity and the excessive fat relating to the body mass of the members of YMCA. The sample consisted of 648 subjects, of which were 341 of feminine gender and 307 masculine gender, with the age to 10 between 87 years old. The frequency overweight, analyzed by the body mass index, was 34,0% (IC =29,1 - 39,2) to the feminine gender and 42,0% (IC = 36,6 47,6) to the masculine gender. The frequency 95% 95% abdominal obesity, analyzed by the waist circumference, was 36,4% (IC = 31,4 41,6) to the feminine gender and 18,9% (IC = 95% 95% 14,8 23,6) to the masculine gender. The frequency excessive fat relating to the body mass, analyzed by the percent body fat, was 76,2% (IC = 71,5 80,5) to the feminine gender and 67,1% (IC = 61,7 - 72,2) to the masculine gender. Considering the 95% 95% evidence presented, as well as the frequencies observed in this study, especially to the excessive fat relating to the body mass, interventionist actions must be taken with the aim of conserving and/or improve the state of health of the individual and collective of the members of YMCA. Moreover, the operational definitions for obesity should be better studied.